Pertamina EP Ramba Field's Multidimensional Collaboration Towards a Clean and Healthy Keluang Village (SIMBA KUAT) - Setiawan, Hanif; Kevin Prayoga, Dedo; Novianti, Leni; Firmansyah, Anton; Ratnasari, Dewi (Pelopor Publikasi Akademika, 2025)
Low awareness of the importance of cleanliness and health is a complex problem in the community. This study aims to analyze the effectiveness of the SIMBA KUAT program's multidimensional collaboration model in addressing issues such as poor infrastructure accessibility, low formal education, stunting cases, traditional childbirth, and wood waste management. Through a mixed-method explanatory sequential approach that combines quantitative and qualitative data. The results show that the program has a significant impact. The overall Community Satisfaction Index (IKM) was 3.85 (96.25%), with a 35% increase in student skills through curriculum integration, a 13% decrease in stunting, a 50% increase in visits by pregnant women through the An-Nur Integrated Health Post (Posyandu), a 30% increase in agricultural production, a 25% increase in income at the Kekar Gemilang Agro Ponik Farmers Group, and a 40% reduction in waste and savings of IDR 500,000/month at the Kekar Gemilang Waste Bank, with an SROI of IDR 1.9 per IDR 1 investment. However, the sustainability IKM score of 3.70 emphasizes the need for funding diversification and digitalization. SIMBA KUAT, facilitated by